2019
DOI: 10.1177/1475090218825178
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic characteristics of a submerged trapezoidal artificial reef unit

Abstract: Submerged structures serve as wave attenuators and are widely adopted for protecting the coast against erosion or to reduce forces on structures situated on its leeward side. Conventional submerged breakwaters are composed of rubble stones, and the sources for quarrying such stones have depleted drastically over a period of time. The artificial reefs are a replacement for submerged breakwaters formed by natural rocks due to its minimum impact on the marine environment, flexibility in molding to any desired sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Besides, the problem is more approachable in a simplistic way using MBEM. Further, the numerical results of a single reef are compared to the experimental results of Lokesha et al 18 in Figure 4 18 which mainly differs from the non-uniform porosity maintained on the surface of the reef unit. On the contrary, the discharge relation given in equation 7is obtained based on the assumption that porosity is uniform throughout the reef boundary.…”
Section: Validation Of the Bem Code Having Quadratic Pressure Drop Bomentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the problem is more approachable in a simplistic way using MBEM. Further, the numerical results of a single reef are compared to the experimental results of Lokesha et al 18 in Figure 4 18 which mainly differs from the non-uniform porosity maintained on the surface of the reef unit. On the contrary, the discharge relation given in equation 7is obtained based on the assumption that porosity is uniform throughout the reef boundary.…”
Section: Validation Of the Bem Code Having Quadratic Pressure Drop Bomentioning
confidence: 99%
“…Porous boxes (rectangular or trapezoidal cross-sections) that serve as artificial reefs can be deployed in the nearshore regions to serve the purpose of increasing both the marine life and at the same time mitigate the wave energy transmission. Recently, experimental investigations on a single submerged artificial reef unit are carried out by Lokesha et al 18 In this study, the authors have examined the effect of perforations on wave transmission and reflection by a submerged trapezoidal artificial reef in regular and random waves. The experiments were performed on models with a crest width of 0.2 m and crest height of 0.4 m and for three different degrees of submergence of 1.5, 1.38 and 1.25 by changing the water depths, d. It is found that the decrease in relative submergence ratio decreases wave transmission and increases the wave reflection for a wide range of wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wave transmission at coastal structures has been studied by a large number of researchers (e.g. Sollitt and Cross, 1972;Daemen, 1991;d'Angremond et al, 1996;Seabrook and Hall, 1998;Bleck and Oumeraci, 2001;Calabrese et al, 2002;Briganti et al, 2003;Van der Meer et al, 2005;Van Oosten et al, 2006;Koutandos et al, 2006;Buccino and Calabrese, 2007;Makris and Memos, 2007;Panizzo and Briganti, 2007;Goda and Ahrens, 2008;Tomasicchio et al, 2011;Metallinos et al, 2016;Mahmoudi et al, 2017;Lokesha et al, 2019;Brancasi et al, 2022;Le Xuan et al, 2022;Kurdistani et al, 2022;. For a discussion of the various wave transmission studies see the latter two studies.…”
Section: Wave Transmissionmentioning
confidence: 99%
“…However, the selection of its type, the distribution of its place, the safety of structure and materials, and the effect of fish aggregation and shelter are the essential prerequisites for fish spawning and conservation zones. Further understanding of the hydrodynamic characteristics around artificial reefs is beneficial to analyze the above effects and proliferation (Jiangtao et al, 2014;Lokesha et al, 2019). Generally, the flow field effect and the stability of artificial reefs are the representative factors reflecting their performance.…”
Section: Significance Of Artificial Reef Constructionmentioning
confidence: 99%